Endothelial dysfunction and pathophysiological correlates in atrial fibrillation. Issue 2 (24th December 2008) - Guazzi, M; Arena, R
Abstract : Endothelial dysfunction (ED) increases oxidative stress and proinflammatory agents, and impairs nitric oxide (NO)-dependent vasorelaxation. Atrial fibrillation (AF) is a risk factor for ED as documented by (1) impaired acetylcholine-mediated blood flow increase; (2) reduced plasma nitrite/nitrate levels; (3) additive impairment of flow-mediated dilatation by comorbidities causing ED; and (4) efficacy of cardioversion. Several possible mechanisms sustain the AF-ED association: (1) An impaired rheology. Endothelial NO release is tightly regulated by laminar shear stress and AF induces a turbulent flow which may impair arterial vessel distension and responsiveness. Specifically, Ca 2+ elicits NO synthase (eNOS) activation, and shear stress application to endothelial cells increases intracellular Ca 2+ primarily in response to regular pulsatile flow at a rate higher than that observed in the presence of oscillatory pulsatile flow. (2) The atrium activity on arterial vessels. The left atrium produces NO and may serve as an endocrine organ releasing nitroso compounds. A disorganised atrial contraction markedly reduces eNOS expression. (3) AF induces atrial inflammation and elevation of C reactive protein and cytokines, exerting a proinflammatory activity on endothelial cells. (4) Systemic factors such as the renin-angiotensin system (RAS) may be prominent. In fact, RAS and inflammation reciprocally "cross-talk". Angiotensin II increases atrial cell death and RAS contributes to myocardial and vascular oxidative stress in AF. RAS inhibition prevents AF. Important clinical correlates of ED in AF patients are muscle underperfusion, premature lactic acidosis and ergoreflex oversignalling during physical activity. This review focuses on the evidence of an association of AF with ED, the possible underlying mechanisms and the pathophysiological correlates.